Exploring challenges to nutrition intervention adherence using COM-B model among patients with wet age-related macular degeneration: a qualitative study. Issue 11 (29th November 2022) - Bian, Wei; Wang, Zonghua; Wan, Junli; Zhang, Feng; Wu, Xuemei; Li, Xin; Luo, Yu
Abstract : Objectives: To explore challenges to nutrition intervention adherence using the Capability, Opportunity and Motivation-Behaviour (COM-B) model among wet age-related macular degeneration (AMD) patients. These factors should be considered in the development of potential support and intervention programmes to address these problems. Design: A qualitative study was conducted with one-to-one and face-to-face interviews with wet AMD patients using a semi-structured question guide. Data were analysed based on COM-B model: capability (physical and psychological), opportunity (physical and social) and motivation (reflective and automatic). Setting: Southwest Hospital of Chongqing Province in China. Participants: A convenient and purposive sample of 24 wet AMD patients were recruited. Results: The themes and subthemes were identified: psychological capability: (1) insufficient knowledge of nutrition; (2) misconceptions about the disease and treatment; (3) knowledge conflict; physical capability: (1) physical restriction; (2) limited access to nutrition knowledge; physical opportunity: (1) communication between providers and patients; (2) health insurance and extra charges; (3) food environment; social opportunity: (1) stigma of disease; (2) family influence; reflective motivation: (1) self-efficacy; (2) attitude; (3) outcome expectancies; (4) lack of professional support; automatic motivation: (1) difficulties in changing eating habits; (2) mindset. Conclusion: Medical staff should pay much attention to the process of patients' nutrition intervention. In addition, it is also necessary to develop professional and internet-based intervention to modify the dietary behaviour and improve the management skills of the patients.